PENGGUNAAN LAHAN PERTANIAN BERDASARKAN KOMODITAS UNGGULAN DI KABUPATEN GOWA - Anwar Anwar (Percetakan Umi Toaha Makassar, 2018)
The development of agriculture in regional autonomy faces various challenges, both internal and external factors of the region, such as the issue of social inequality and globalization issues. This social and globalization issue demands each region to be able to compete at home and abroad. The gap and globalization has implications for provinces and districts to develop the region and its flagship product. The development of agriculture is one of the sectors that should be the main priority in the development of agribusiness-oriented areas, high productivity, efficient, sustainable, and sustainable. The success of agricultural development determined by the environment in which agricultural commodities are grown, such as food crops, horticulture, plantations, and livestock. This study aims to: (1) know the use of land that can support productivity in Kecamatan Tinggimoncong, and (2) analyze the sector that developed into the leading sector in agricultural development in Kecamatan Tinggimoncong. Based on the use of lahandi Kecamatan Tinggimoncong consist of settlement area, secondary forest, dry land, paddy field, shrubs and open land. The analysis results of Commodity Excellence Revealed (KKT) there are fourteen superior commodities: rice, sweet potato, leek, potato, cabbage, cabbage, tomato, robusta coffee, arabica coffee, cloves, hazelnut, pepper, and vanilla.